THE LIFESPAN OF NURSING EDUCATION IN CAMBODIA - Virya Koy (Belitung Nursing Journal, 2016)
This paper aims to explain the lifespan of nursing education in Cambodia, which has been up and down for over 66 years. The journey of Cambodian nursing education is fulfilled by many challenges faced by nursing leaders in the country, including the challenges caused by the decades of civil war devastated Cambodian society. It takes high responsibility and needs more powers, skills, and commitments to produce competent professional nurses to fulfill the tasks in the clinical settings through nursing education, and it is characterized by the progress in responding societal needs of the society.